Assessing the agronomic efficiency of rock dust as a nutrient source in agriculture - de Figueiredo Oliveira, Caroline (2025)
Silicate rocks derived from mining waste, particularly siltstone powder, have the potential to function as a nutrient source in agriculture. It is worth noting that their effectiveness can be enhanced when combined with limestone. This study aimed to assess the agronomic efficiency of using siltstone powder in controlled environments. The experiment utilized soils with different textures (Typic Quartzipsamment (TQ) and Oxisol (OX)). The soils were incubated with doses of rock dust (0, 4, 8, 16, and 32 t ha−1) for 60 days, followed by chemical attribute analysis. Subsequently, four separate pot experiments were conducted, involving maize and bean cultivation with four replications. During plant flowering, the production of dry mass and accumulation of macronutrients and micronutrients were evaluated. TQ soil with the highest dose of rock dust exhibited significantly higher levels of potassium, calcium, and magnesium compared to untreated samples: ten, twenty, and eight times higher, respectively. Ox samples with the highest dose showed double the levels of magnesium, and four times the levels of potassium and calcium compared to untreated soil. The highest dose of rock dust increased pH by 49% in sandy soil and 38% in medium soil. Maize plants showed 40% and 200% increases in shoot dry matter in TQ and OX, respectively, at the lowest rock dust dose. Similarly, bean plants showed 126% and 283% increases in shoot dry matter in TQ and OX, respectively, at the lowest rock dust dose. The rock dust shows promise as a nutritional management option for crop cultivation.